A semi qualitative study on the perception of the general public to the presence of the first COVID-19 patient in the locality - Kathiravan, Sanjana; Reddy, Sai Chaitanya; Singh, Shubh Mohan (International Journal Of Community Medicine And Public Health, 2022)
Background: Infectious diseases have had a significant role in shaping human history by engraving a subconscious sense of ‘fear of infection’. The three sequential stages of the rational response to fear- fear, denial, and frustration, have been reported among quarantined individuals during any outbreak. To our knowledge, this was one of the first studies to assess the impact of the first case of coronavirus disease 2019 (COVID-19) among the neighbouring dwellers. Methods: A semi-qualitative study using semi-structured in-depth telephonic interviews was conducted after ethical committee approval. Results: All the participants were aware of the correct attitudes and practices to be followed during the pandemic. Mixed reactions of panic, fear and confusion were observed. Most participants were concerned about elderly at home and financial constraints. Despite most participants having minimal fear of contracting the illness themselves, fear of a family member acquiring the same seemed to be higher. Conclusions: The study adds to the existing literature that fear and anxiety during a pandemic are mostly due to the uncertainty related to the disease spread and misinformation. There is a need for phased and well informed lockdown implementation and better knowledge propagation among the general public in order to mitigate unwanted fear and panic among the general public.